ETHNOGRAPHIC PERSPECTIVES ON INDIGENOUS KNOWLEDGE SYSTEMS IN TAMIL SOCIETY - Balasubramani. S (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study examines indigenous knowledge systems in Tamil society through an ethnographic framework, with attention to the lived practices of region-specific and occupation-based communities. It analyses the transmission of knowledge embedded in oral traditions, ritual practices, ecological management, and artisanal production. Particular focus is given to domains such as ethnomedicine, agricultural cycles, water management, and sacred landscapes, where empirical observation and inherited wisdom converge. The study situates these knowledge systems within caste-based and kinship-structured social organization, demonstrating that knowledge is not abstract but socially embedded and functionally adaptive. It also considers the pressures exerted by modernization, state policy, and market integration, which have altered the modes of transmission and authority of traditional knowledge holders. By integrating field-based observations with historical and anthropological analysis, the study argues that indigenous knowledge in Tamil society constitutes a dynamic and context-sensitive intellectual tradition rather than a static residue of the past.